Nature of radioactivity of quarry drainage waters in the Novosibirsk region - A. S. Derkachev; A. A. Maksimova; D. A. Novikov; F. F. Dultsev; A. F. Sukhorukova; A. V. Chernykh; A. A. Khvashchevskaya (Горные науки и технологии, 2022)
This study is relevant for obtaining the first geochemical data (including information on radionuclides) on the drainage waters of developed and flooded quarries in the eastern areas of the Novosibirsk Region. The objective of the study was to identify the features of the chemical composition of drainage waters (a wide range of chemical elements from Li to U). The study was carried out by titrimetry, ion chromatography and mass spectrometry with inductively coupled plasma in a laboratory setting at the Hydrogeochemical Problem Research Laboratory (PNIL GGH) of the Engineering School of Natural Resources of Tomsk Polytechnic University (IShPR TPU). Measurements of 222Rn in waters were carried out at the Alfarad Plus facility of the Laboratory of Siberian Sedimentary Basins Hydrogeology of the A. A. Trofimuk Institute of Petroleum Geology and Geophysics, Siberian Branch of the Russian Academy of Sciences (INGG SB RAS). The data were divided into homogeneous geochemical populations using the coefficients Ca / Na, Ca/ Mg, Ca / Si, Mg/ Si, Na / Si. The chemical composition of the studied objects was found to be highly diverse. The dominant waters have the chemical formula SO4-HCO3 / Na-Mg-Ca with a TDS (total dissolved solids) of 400 to 700 mg/dm3. Three geochemical groups of waters were identified. The first is represented by drainage waters of the developed rubble stone quarries, the second includes facilities of the Gorlovka coal basin, and the third refers to abandoned flooded quarries. The first group is characterized by oxidizing conditions with Eh varying over a wide range from +84.6 to +261.0 mV, pH from 6.9 to 8.6, and O2dissoived from 3.43 to 14.39 mg/dm3. The radionuclide concentrations are (mg/dm3): 238U 9.30 • 10-3 - 1,40; 232Th 1,00 • 10-6 - 2,16 • 10-3; 222Rn activity varies from 1 to 572.5 Bq/dm3. The 232Th / 238U ratio ranges from 4.20 • 10-5 to 2.69 • 10-3 with an average of 8.40 • 10-4. The second group has a smaller Eh variation range of +133.2 to +199.6 mV, pH from 7.5 to 8.5, and O2dissolved from 6.81 to 10.43 mg/dm3. The radionuclide concentrations vary in the following ranges (mg/dm3): 238U 2.26 • 10-3 - 2.90 • 10-2; 232Th 7.5 • 10-6 - 5.57 • 10-4. The 232Th / 238U ratio ranges from 8.37 • 10-4 to 4.80 • 10-2 at an average of 9.54 • 10-3. The third group is also characterized by an oxidizingizing geochemical environment with Eh +131.3 - +250.0 mV, pH from 6.9 to 8.8 and O2dissolved from 4.00 to 16.59 mg/dm3. The radionuclide concentrations are (mg/dm3): 238U 3.00 • 10-4 - 2.74 • 10-2; 232Th 1.65 • 10-6 - 1.15 • 10-5; 222Rn activity varies from 2 to 31 Bq/dm3. The 232Th/ 238U ratio ranges from 2.36 • 10-4 to 1.02 • 10-3 at an average of 6.25 • 10-4. Overall, the 232Th / 238U ratio of the studied waters indicates their uranium nature of radioactivity. The data obtained indicate a slight impact of the drainage water discharge from the abandoned quarries on the environment.